Wheat in Kenya: toward self-sufficiency or toward broader development goals - Snyder, Katherine; Muindi, Pauline; Khaemba, Colleta; Rutsaert, Pieter; Mutegi, Judy; Omondi, Francis; Donovan, Jason (Frontiers in Sustainable Food Systems, 2025)
The conflict between Russia and Ukraine, and the associated disruptions in global wheat supply has resulted in concern for food security throughout sub-Saharan Africa. In Kenya, which depends heavily on wheat imports to meet demand, this concern has intensified calls for self-sufficiency in wheat production. Wheat shortages have led to price hikes that hit all consumers but the urban poor in particular. To decrease reliance on imports, for both food security and for nutrition, Kenya has implemented policy measures to spur increased wheat production. This paper explores the context for increasing wheat production in Kenya to respond to increasing demand, and for addressing the needs of the stakeholders in the sector. Findings suggest that wheat self-sufficiency is unlikely to be achieved soon. Major public and private investments would be required to build the infrastructure, systems, and institutions required to support smallholders to expand and intensify their production. Millers have relied on cheap wheat imports for decades and show limited signs of willingness to support backward linkages with farmers. Critical public infrastructure (e.g., wheat seed systems, extension systems) is ill-equipped to support the growth of the wheat sector. Researchers and policy makers would better serve the interests of smallholder wheat growers by identifying feasible objectives for sustainable and equitable industry growth. We conclude with recommendations for targeted investment and interventions.